Atrial fibrillation as a complication of endovascular patent foramen ovale closure: a clinical trial - A. S. Tereshchenko; G. K. Arutyunyan; E. V. Merkulov (Российский кардиологический журнал)
One of the known potential complications associated with endovascular closure of the patent foramen ovale (PFO) is de novo atrial fibrillation (AF).Aim. To assess the risk factors and incidence of de novo AF in patients who underwent endovascular PFO closure.Material and methods. The data of 276 patients who underwent endovascular PFO closure for the period from 2020 to 2023 at the Chazov National Medical Research Center of Cardiology were analyzed. All patients underwent examinations in accordance with clinical guidelines. De novo AF in the postoperative period was assessed by Holter monitoring, while 1, 6 and 12 months after the intervention — by electrocardiographic recording. Based on univariate regression analysis, risk factors associated with de novo AF were identified.Results. De novo AF in the postoperative period was registered in 2 patients. One month after the intervention, AF episodes were diagnosed in 6 patients. After 6 months, AF detected earlier persisted in 3 patients,and there were 3 new cases. Twelve months after the intervention, AF was recorded in 2 patients. According to regression analysis, the following parameters were associated with de novo AF: age ≥52,0 years (hazard ratio (HR) 6,22; 95% confidence interval (CI): 1,51-25,56), body mass index ≥28,07 kg/m2 (HR 8,48; 95% CI: 1,72-41,73), CHARGE-AF score ≥0,56 (HR 4,59; 95% CI: 1,12-18,82), left atrial size ≥4,00 cm (HR 19,56; 95% CI: 2,10-181,88), LAVi ≥34 ml/m2 (HR 45,67; 95% CI: 5,46-381,83) according to echocardiography.Conclusion. Echocardiographic signs of left atrial and left ventricular dilation were significantly associated with a high risk of de novo AF in the immediate and longterm periods after endovascular PFO closure.